Overgeneration Shedding Simulation Using Digsilent at the New Aurduri 500KV and Betung 275KV Extra High Voltage Substations - Anggoro Indra Kusuma Atmaja; Rahmaniar Rahmaniar; Muhammad Erpandi Dalimunthe (INFOKUM, 2026)
The reliability of the electric power system is greatly influenced by the system's ability to maintain the loading of the main equipment within safe limits during a disturbance. In the Sumbagselteng system, conductor disturbances have the potential to cause excessive loads on the Inter Bus Transformer (IBT) due to the concentration of generation in the South Sumatra region. Therefore, the implementation of the Over Generation Shedding (OGS) scheme is required as part of the defense scheme to protect the IBT from overloading conditions. This study aims to analyze the effectiveness of the OGS scheme in limiting the fault current and improving the dynamic stability of the system. The method used is a dynamic simulation using DigSILENT software with a short circuit fault scenario and a two-stage generator shedding based on definite time characteristics. The parameters analyzed include the IBT current, loading percentage, rotor angle, logarithmic decrement, and damping ratio. The simulation results show that the IBT current increases to around 1800 A with a loading reaching 110–133% during the disturbance. After the 340 MW generator shedding in two stages, the current drops to around 490 A and the loading returns below 65%. The damping ratio ranged from 0.017 to 0.069, indicating the system remained stable with improved damping. The OGS scheme proved effective in reducing IBT loading and improving system stability under disturbance conditions.